Influência da geometria da nanocarga na estruturação, orientação e propriedades de filmes tubulares de nanocompósitos de PA6 - Marini, Juliano (2012)
The structure and morphology of polymers and consequently their properties are dependent on the processing conditions. During the blown film process, high shear and elongational flows can induce a preferred orientation of the polymer chains; controlling the process conditions, it is possible to obtain films with anisotropic properties. Polymeric nanocomposites have attracted industrial and scientific interest due the possibility of obtaining materials with improved thermal, mechanical, and permeation properties by the addition of small contents of inorganic fillers. This dispersed phase can also be affected by the processing conditions and also develop a preferred orientation, and influence the three-dimensional structure of the composite and its properties. In this work, the influence of the nanoparticle s (NPs) shape and processing conditions on the structure (with emphasis on the orientation characteristics) of polyamide 6 (PA6) nanocomposites blown films was evaluated, by the incorporation of an one-dimensional NP (halloysite HNT, with a hollow tubular structure) and a two-dimensional NP (montmorillonite MMT, with lamellar structure) to the polymeric matrix. Using a constant NP content (fixed above the theoretical percolation threshold) and evaluating the presence or absence of the NP s superficial treatment, blown films were obtained in four different processing conditions, varying the take-up and blow-up ratios (TUR and BUR, respectively) and using a fixed mass flow. Unexpectedly, all the films exhibited a preferred orientation of the crystalline lamellae along the normal direction, i.e., along the film thickness, independently of the processing conditions. This behavior was explained by the cooling conditions and initial preferred orientation of the polymer chains in the annular die exit. On the other hand, the NPs presented a preferred orientation along the flow direction and were well distributed and dispersed through the matrix. The film s thermal dynamicviii mechanic, tensile, permeation and optical behaviors were consistent with the structure observed and significant improvements of these properties were achieved for the films of organically treated HNT and MMT PA6 nanocomposites. Regarding the NP s shape, greater aspect ratio and surface area, in the presence of good interfacial interactions, promoted a greater efficiency of reinforcement.